2021
DOI: 10.5430/ijfr.v12n5p80
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Influence of Commodity Prices, Real Exchange Rate and Trade Openness on Economic Performance in an Emerging Country

Abstract: Do commodity prices, real exchange rate and trade openness influence economic growth in South Africa? This question is fundamental to academic research since it forms the basis of macroeconomic policies. Therefore, the comprehension of such a relationship is vital which has ushered this study into investigating the effect of real exchange rate, commodity prices and trade openness on economic growth in South Africa from 1984-2019. The purpose of this study is to contribute to the diverse literature on macroecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Called immiserizing growth, this is a long-term phenomenon that occurs when the gain in a country's social welfare arising from economic growth is more than offset by the loss in such welfare associated with an adverse shift in the terms of trade (Bhagwati, 1958). Additionally, in South Africa, Ntshwe and Garidzirai (2021) revealed that commodity prices and trade openness increase economic growth when all other things are held constant by employing the Johansen co-integration method and Vector Error Correction Model (VECM) to data from 1984 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Called immiserizing growth, this is a long-term phenomenon that occurs when the gain in a country's social welfare arising from economic growth is more than offset by the loss in such welfare associated with an adverse shift in the terms of trade (Bhagwati, 1958). Additionally, in South Africa, Ntshwe and Garidzirai (2021) revealed that commodity prices and trade openness increase economic growth when all other things are held constant by employing the Johansen co-integration method and Vector Error Correction Model (VECM) to data from 1984 to 2019.…”
Section: Literature Reviewmentioning
confidence: 99%